(untitled) (Global Journal of Management and Business Research, 2022)
Having always occupied a place of choice in any organization at world, the human being is the key to all its steps, it determines the direction it borrow; both success and failure are intrinsic to it. Thus, should we develop and mobilize the required skills that each individual abounds, in order to put them at the structural arrangement in order to achieve desired results. To achieve this, it is therefore necessary to the organization, to appropriate and control its workforce.